(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
The employment of wood as a raw resource linked with wood industry sectors is rising with population growth. Nevertheless, wood availability is declining. Producing sandwich boards (SB) with biomass resources could solve the issue. Oil palm trunks (OPT) can be transformed into high-value products and are readily available by replanting. In the current study, SB is modified by employing OPT as the core material and veneers as the face and back of OPT particle board and light hardwood veneers (LHW), including Kembang Semangkuk, Mempisang, and Pulai. The SB manufactured in this study was laminated with various veneers. The present study also utilized phenol formaldehyde resin at a 300 g m−2 spreading rate, while the sheet was pressed at 120°C and 130°C for 150 s and 180 s under 150 psi. The physical and mechanical properties of the resultant SB were evaluated according to the Japanese Industrial Standards (JIS) A 5908 (2003) standard. Surface soundness assessment was performed per the EN 311 (2002) requirements. The results indicated that the different veneer species significantly affected the SB rupture modulus, elasticity modulus, and surface soundness (SS) parameters. The different press temperatures employed also influenced the thickness swelling (TS) and specific strength of the board. The boards exposed to 120°C met all JIS standards, except for the TS parameters. Furthermore, the SB incorporated with Mempisang as the surface material demonstrated considerable surface soundness.